2008
DOI: 10.1097/mlg.0b013e318185793ds
|View full text |Cite
|
Sign up to set email alerts
|

The GNAS1 T393C Polymorphism Predicts Survival in Patients With Advanced Squamous Cell Carcinoma of the Larynx

Abstract: The T393C SNP is a prognostic marker that could help to identify high risk patients suffering from head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Gastric cancer is the fourth most common cancer with [15] 2008 157 Survival was significantly dependent on the T393C genotype in advanced American Joint Committee on Cancer (AJCC) stages (Ⅲ-Ⅳ) with higher 5-yr survival rates for TT, followed by TC and CC (P = 0.0437)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer is the fourth most common cancer with [15] 2008 157 Survival was significantly dependent on the T393C genotype in advanced American Joint Committee on Cancer (AJCC) stages (Ⅲ-Ⅳ) with higher 5-yr survival rates for TT, followed by TC and CC (P = 0.0437)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that increased expression of Gαs enhances apoptosis [7,8] and that Gαs mRNA expression is different between T393C genotypes [9] . For various solid tumors, previous studies demonstrated that patient survival and tumor progression depended on T393C genotype [10][11][12][13][14][15][16][17] . Until now, nothing has been published about the impact of the GNAS1 T393C polymorphism on gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that a common synonymous single nucleotide polymorphism (SNP) in exon 5 (T393C) of the GNAS1 gene is associated with the prognosis of human malignancies [3][4][5][6][7]. Frey et al [8] have showed the genotypes of the GNAS1 T393C polymorphism are associated with altered G s expression.…”
Section: Introductionmentioning
confidence: 98%
“…The Gs protein subunit (GNAS1) gene has been found to play an important role in promoting tumor cells apoptosis [3]. There is increasing evidence that a common synonymous single nucleotide polymorphism (SNP) in exon 5 (T393C) of the GNAS1 gene is associated with the prognosis of human malignancies [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension (Jeunemaitre et al 1992) and CAD severity Tumor development and prognosis in several types of tumours (Alakus et al 2009;Lehnerdt et al 2008;Frey et al 2005aFrey et al , b, 2006 0 = TT, 1 = CT, 2 = CC…”
Section: Methodsmentioning
confidence: 99%